Pengaruh Pola Asuh Demokratis Orang Tua dan Kepribadian Guru terhadap Karakter Siswa Kelas III SD Se-Gugus Kartini - Astuti Prasetyaningsih; Rokhmaniyah Rokhmaniyah; Muhammad Husni (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
Building the students characteristics is one of the goals of national education of Indonesia. This study aims to determine the effect of democratic parenting of parents and teacher personality to the characteristics of the third grade elementary school students in the Kartini Cluster, Purworejo District. This research is a quantitative research that uses the regression method. Based on the data analysis, it can be concluded: 1) There are a positive and significance effects between democratic parenting of parents to the students characteristics. 2) There are a positive and significance effects between the teacher personality to the student characteristics. 3) There are a positive and significance effects between the democratic parenting of parents and the teacher personality to the students characteristics. This proved that there are a positive and significance effects of the three research variables, namely democratic parenting of parents, teacher personality, and students characteristic.